2016
DOI: 10.1016/j.pcad.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of high density lipoprotein deficiency

Abstract: Low serum high density lipoprotein cholesterol level (HDL-C) < 40 mg/dL in men and < 50 mg/dL in women are a significant independent risk factor for cardiovascular disease (CVD), and are often observed in patients with hypertriglyceridemia, obesity, insulin resistance, and diabetes. Patients with marked deficiency of HDL-C (< 20 mg/dL) in the absence of secondary causes are much less common (< 1% of the population). These patients may have homozygous, compound heterozygous, or heterozygous defects involving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 42 publications
(97 reference statements)
1
64
2
Order By: Relevance
“…Neurological symptoms represented the prevalent clinical sign in the proband. It has been reported that several different inherited defects involving the apolipoprotein (APO)AI, ABCA1, or lecithin:cholesterol acyl transferas (LCAT) genes may be responsible for FHD (24). Also APOA1-related amyloidosis is characterized by a small fiber neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological symptoms represented the prevalent clinical sign in the proband. It has been reported that several different inherited defects involving the apolipoprotein (APO)AI, ABCA1, or lecithin:cholesterol acyl transferas (LCAT) genes may be responsible for FHD (24). Also APOA1-related amyloidosis is characterized by a small fiber neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Homozygous or compound heterozygous apolipoprotein A-I deficiency has been described in less than 20 patients worldwide and is characterised by an almost Review complete deficiency of HDL cholesterol (<0·3 mmol/L or <10 mg/dL) and apolipoprotein A-I (<0·1 g/L) and, in most individuals, premature coronary heart disease. [79][80][81] Patients with two null alleles have xanthomas, either limited to the eyelids, or covering the body (figure 2). [79][80][81] Patients with homozygous or hemizygous missense mutations have residual plasma concentrations of a structurally abnormal apolipoprotein A-I, and can show corneal clouding, similar to familial LCAT deficiency and fish-eye disease.…”
Section: Apoa1 Mutationsmentioning
confidence: 99%
“…[79][80][81] Patients with two null alleles have xanthomas, either limited to the eyelids, or covering the body (figure 2). [79][80][81] Patients with homozygous or hemizygous missense mutations have residual plasma concentrations of a structurally abnormal apolipoprotein A-I, and can show corneal clouding, similar to familial LCAT deficiency and fish-eye disease. [79][80][81] However, this feature is inconsistently observed in patients with complete apolipoprotein A-I deficiency, sometimes detectable only by slit lamp examination.…”
Section: Apoa1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic deficiency for ABCA1 reduces the plasma levels of HDL cholesterol (HDL-C), one of the parameters associated with higher risk for cardiovascular disease. 150,151,167 In mouse models of atherosclerosis, macrophage-specific deletion of ABCA1 resulted in a large accumulation of cholesterol in macrophages, and exacerbated atherosclerosis in the advanced stage of disease. 168 ABCA1 also protects macrophages from undergoing apoptosis after the engulfment of apoptotic cells, and it may do so in two ways.…”
Section: Breakdown Of Macrophage Lipid Metabolism-the Case Of Athermentioning
confidence: 99%